Clinical study of anatomical ACL reconstruction using a rounded rectangular dilator - Nakase, Junsuke (BMC Musculoskelet Disord, 2021)
BACKGROUND: The aim of this study was that to compare clinical results between the rounded rectangular femoral tunnel ACL reconstruction (RFTR) and the conventional round femoral tunnel ACL reconstruction using a hamstring tendon. The hypothesis was that ACL reconstruction performed using the rounded rectangular dilator technique was better than that performed using the conventional round femoral tunnel technique in terms of clinical results and bone tunnel enlargement. METHODS: We conducted retrospective study. After exclusions, 40 patients were included in the conventional anatomical single-bundle ACL reconstruction (ASBR) group and 40 patients were included in the RFTR group. The evaluation items were knee stability, Lysholm knee score, IKDC subjective score at 2 years after surgery and bone tunnel enlargement. RESULTS: The RFTR group had a larger femoral tunnel area (average area, 53.1 ± 4.0 mm(2) vs. 46.1 ± 7.0 mm(2); P < 0.01), better anteroposterior stability, and higher Lysholm scores than the ASBR group (average side-to-side difference for anterior tibial translation, 0.6 ± 0.8 mm vs. 1.6 ± 1.4 mm; P < 0.01; average Lysholm score, 98.5 ± 2.1 vs. 97.5 ± 3.5; P < 0.01). Further, bone tunnel enlargement ratio was significantly lower in the RFTR group (73 ± 38% vs. 107 ± 41%; P < 0.01). CONCLUSIONS: We designed and developed an original rounded rectangular dilator to perform a novel ACL surgery. This technique can create a larger bone tunnel and improve clinical results than the conventional round anatomical single-bundle ACL reconstruction.